A225 A NEW STANDARD: AN OPEN-LABEL TRIAL EXAMINING THE EFFECTIVENESS OF INDIVIDUALIZED WEB BASED COLONOSCOPY PREPARATION INSTRUCTION. (1st March 2018) - Nap-Hill, E; Suzuki, M; Galorport, C; Yonge, J; Amar, J; Bressler, B; Ko, H; Lam, E; Ramji, A; Rosenfeld, G; Telford, J J; Whittaker, S; et al.
Abstract: Background: Non-pharmalogical factors such as patient education have been shown to significantly improve bowel preparation quality for colonoscopy. For the endoscopist, optimal bowel cleaning increases cecal intubation rates, increases adenoma detection rates, and minimizes necessity for repeat procedures. Following a randomized study demonstrating that the web based patient education tool was superior to traditional paper instructions, this study aims to implement the program at a larger scale; a real life scenario. Aims: To determine the effectiveness of web-based pre-colonoscopy instructions for patients, as measured by the percentage of patients achieving an excellent level of colon cleanliness, equivalent to Boston Bowel Preparation Score (BBPS) ≥ 8. Secondary goals were to assess the patient satisfaction and practicality of this means of education being used by the entire GI clinic for all outpatient colonoscopies. Methods: Prospective, single center, open label study. Adult outpatients scheduled for non-urgent colonoscopy, aged 19 or greater with English proficiency or an available family member/friend who can translate the instructions for them who have a functioning email account were recruited for this study. Patient demographics, cancellations, and quality of bowel preparation (assessed using Boston and Ottawa Bowel preparation scales) were collected. Patient satisfaction surveys were completed the day of their colonoscopy before their procedure to assess clarity and usefulness of the standardized online instructions. Results: Finalized data analysis (n = 900) shows that 84.5% of patients have achieved a score demonstrating adequacy on the BBPS (mean 7.0; adequate score considered ≥ 6 and 90.1 % have scored adequately on the OBPS (mean 3.4; adequate considered ≤ 7). 94.2% of patients scored the web education tool as "Very Helpful" (8 or higher out of 10 on our usefulness scale), and 92.1% scored as "Very Clear" (8 or higher in terms of the clarity of information presented to them). Conclusions: Our analysis suggests that the online instruction pathway is a sufficient alternative to paper instruction, and can be effectively utilized as a standard of care in a real life scenario. Although we did not attain the excellent score (BBPS) ≥ 8, the majority of our preparations were adequately prepared. Our instruction methodology also presents advantages compared to paper because it is uniquely modified for each patient and limits the instruction required by an assistant. Patient satisfaction scales have demonstrated an overwhelming majority of patients who are very satisfied with the clarity and helpfulness of the program. Funding Agencies: None